Epigallocatechin-3-gallate Green Tea (Camelia Sinensis) Phytomedicine for Orthodontic Tooth Relapse Prevention: Narrative Review - Ira Arundina, - (Teikyo University School of Medicine, 2021)
Epigallocatechin-3-gallate (EGCG) is an active compound that is abundant in green tea (Camellia sinensis). EGCG has potential as an antioxidant, anti-inflammatory, anti-osteoclastogenesis as well as pro-angiogenic and pro-osteoblastogenesis. Orthodontic tooth relapse (OTR) may occur due to suboptimal alveolar bone remodeling and excessive inflammation during orthodontic tooth movement (OTM) which causes inhibition of periodontal tissue regeneration. EGCG is thought to increase the regeneration of periodontal tissue after OTM so as to prevent relapse. This narrative literature review aimed to describe the potential of the active compound EGCG in green tea phytomedicine as a candidate biomaterial to prevent OTR. EGCG has strong antioxidant potential by being able to reduce High Mobility Group Box 1 (HMGB-1) and Heat Shock Protein-70 (HSP-70) during inflammation. EGCG in green tea can inhibit pro-inflammatory cytokines such as Tumor Necrosis Factor-α (TNF-α) through its antioxidant properties. Osteoclastogenesis can be suppressed by administering EGCG because of the effect of decreasing TNF-α and signaling inhibition of Receptor activator of nuclear factor κ-β (RANK) and Receptor activator of nuclear factor κ-β ligand (RANKL) so that osteoblastogenesis can increase. The increase in osteoblastogenesis after EGCG administration was due to osteoinductive effects such as Bone Morphogenic Protein-2 (BMP-2) activating runt-related transcription factor-2 (RUNX2) and osterix, resulting in osteoblast maturation. Mature osteoblasts secreted bone related proteinfor alveolar bone regeneration such as osteocalcin, osteonectin and osteopontin which can prevent relapse after OTM. EGCG, which is the active compound in green tea (C. sinenis) may potential to be used as phytotherapy for orthodontic tooth relapse.